A Contrastive Analysis Between English and Indonesian Kinds of Sentences - Uktolseja, Lulu Jola; Sujaja, Hamim; Matinahoru, Mario Fridolin (IJET (Indonesian Journal of English Teaching), 2019)
The difference between English and Indonesia language become one of the hardest things to learn and to be understood. It could be seen by the grammar of the language and the system of communication between both languages. The aim of this study is to identify the difference and the similarity sentence between English and Indonesia Language and analysis contrastive between both languages. This study used a qualitative descriptive approach to find out the contrast between both of them. the sample in this study were 20 students of English Department Students in Victory University, especially the 2nd Semester. The result of this study was the main error of the students was in Declarative Sentence (DS), Negative Sentence (NS), Interrogative Sentence (IS) and Exclamatory Sentence (ES) i.e 92.86%. Based on the research, we found out that the students did those errors because the pattern of those sentences are different whereas the Imperative Sentence (IMS) has the same pattern with English.